A viewpoint based extension of the common warehouse metamodel to support the user's viewpoint approach. (2016) - Demraoui, Lamiae; Behja, Hicham; Zemmouri, El Moukhtar; Abbou, Rachid Ben
Metadata integration and interoperability is still one of the leading problems facing the datawarehouse and the business analysis community. The Common Warehouse Metamodel (CWM) enables interoperability and easy interchange of warehouse and business information metadata between heterogeneous systems. However, a decisional process involves a variety of expert and novice users who manipulate several types of knowledge and know-how, each user exploits the process based on his preferences, needs and objectives. Currently, the CWM metamodel does not allow to model and to keep trace of users' experiences during the exploitation of the whole decisional process. In this paper, we extend the CWM in order to support its different users with a new entity that is viewpoints, which models and keeps trace of user preferences, objectives, and decisions made during the datawarehouse process. Our main objective is the capitalisation of users' experiences to enhance reusability of metadata and coordination between users.